ANALISIS PENERAPAN PRINSIP PENGHIMPUNAN DAN PENGALOKASIAN DANA PADA LAPORAN SUMBER DAN PENGGUNAAN DANA LEMBAGA PENGELOLA ZAKAT (STUDI KASUS PADA POS KEADILAN PEDULI UMAT CABANG SURABAYA) - M, RIZQIYATUL (Jurnal Akuntansi AKUNESA, 2013)
This research aims to know the application of the collection and allocation of funds to the sources and uses of funds report on the PKPU foundation. This research used a qualitative descriptive method. In collecting data the authors used interviews and observations. The data used are the primary data and secondary data. Based on the results of research it can be concluded that the PKPU foundation apply to the two principles on the collection and allocation to distribute funds donated. The second principles is the pooling of funds and asset allocation. Keywords: Collection and allocation of funds, Pooling of fund, Asset allocation